Integrated Development of Himalayas- An Approach Paper - Seth, S.L. (Journal of Soil and Water Conservation, 2022)
In order to manage and develop the fragile and unstable eco-system of Himalayas it is necessary to promote development of its components like land, soil, water, vegetation, live stock and human resources. For planning and implementing developmental programmes, needs and strategies should be adjusted to the characteristics of the different situations. Nine such different situations are proposed. Different attributes of the resources management are discussed and involvement of the people and upgradalion of their technical and managerial skill are emphasized.